Sri Lanka : de la lutte contre le terrorisme à la catastrophe humanitaire - Delon Madavan (EchoGéo)
The will of Sri Lankan government to finish militarily with LTTE has ended with an humanitarian catastrophe. Both the Sri Lankan Army and the Tigers are guilty of international war and humanitarian crimes against Tamil civilians, who are trapped in the war zone or locked in detention camps. The different perceptions of the military operation according to the communities should need the creation of an International Penal Court for Sri Lanka